HUBUNGAN PATRON-KLIEN PETANI KARET DAN TOKE DI DESA PEBAUN HULUKECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Pradela, Yunia; Widodo, Teguh (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research was conducted in Pebaun Hulu Village, Kuantan Mudik District, Kuantan Singingi Regency. This research aims (1) to determine the form of relationship between rubber farmers and toke. (2) To find out the factors that influence rubber farmers to maintain their relationship with toke. This research uses qualitative research methods with 7 informants as research subjects taken based on predetermined criteria. The data collection techniques used in this research are observation, interviews and documentation. Based on the research results, it can be concluded that there are four forms of relationship between rubber farmers and toke. This relationship consists of mutually beneficial relationships, personnel relationships, loyalty relationships and reciprocity relationships. This mutually beneficial relationship is a form of relationship where both parties gain benefits and advantages from the existing relationship. Personnel relationships are relationships that are direct and intensive and both parties involved know each other personally. The loyalty relationship is a reciprocal relationship between the patron and the client. This loyalty relationship takes the form of loyalty of the rubber farmer or client to the toke or patron. If we look at the factors that influence rubber farmers to maintain their shape with toke, it consists of two factors. The second factor includes economic factors and also social factors Keywords: Patron-Client Relationship, Rubber Farmers, Toke